Fundamental aspects of CMOS technology: basics, implications, and a roadmap to the future - Foty, D.; Gildenblat, G. (Видавництво Національного університету “Львівська політехніка”, 2004)
Наведено огляд розвитку напівпровідникової технології та сучасний стан розвитку цього напрямку.

In this paper, the critical importance of scaling theory to the success of CMOS technology will be reviewed and evaluated. The history of CMOS shows that scaling theory has been the dominant theme, but that the evolution of the technology has followed different directions at different times due to constraints imposed by scaling theory. This situation is actually best understood by comparison with the theory of punctuated equilibrium, which is a familiar concept in evolutionary biology. The state of present-day constraints will be considered, followed by discussion of some possible options for continuing the progress of CMOS into the future.
Keywords: 638.235.231